1991
DOI: 10.1002/ijc.2910470203
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma‐associated mucin serum markers CA M26 and CA M29: Efficacy in detecting and monitoring patients with cancer of the breast, colon, ovary, endometrium and cervix

Abstract: Two recently developed monoclonal antibody (MAb)-based anti-mucin assays, CA M26 and CA M29, were studied in 250 cancer patients and compared to 3 well-established marker tests, viz., CA 125, CA 15.3 and SCC, in order to assess their clinical usefulness as serum tumor markers. Pre-treatment sera were obtained from patients with predominantly low-stage epithelial malignancies comprising 200 adenocarcinomas (of the ovary, endometrium, breast and large intestine) and 50 squamous-cell carcinomas (of the uterine ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 25 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…MUC‐1 is expressed at the apical surface of most glandular epithelia. It is widely used as a tumor marker for breast cancer, but high serum concentration may also be found in patients with ovarian cancer (16), (17). Serum CA 15‐3 was >32 U/ml in 57.1% of ovarian carcinoma patients, and in detail in 63.9% of patients with non‐mucinous and 16.7% of those with mucinous malignancies (18).…”
Section: Discussionmentioning
confidence: 99%
“…MUC‐1 is expressed at the apical surface of most glandular epithelia. It is widely used as a tumor marker for breast cancer, but high serum concentration may also be found in patients with ovarian cancer (16), (17). Serum CA 15‐3 was >32 U/ml in 57.1% of ovarian carcinoma patients, and in detail in 63.9% of patients with non‐mucinous and 16.7% of those with mucinous malignancies (18).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the lung have also been correlated with mRNA levels of several MUC genes [59], and the levels of mRNA of a number of other MUC genes have been found increased in different cancer tissues (recently reviewed in [60]). Elevated serum levels of CA15-3 [35] and other mucins have been reported in patients with lung, pancreatic, colon, breast and ovary cancer [61]. MRS studies have looked at ovary biopsies where the Fuc IIa and IIb cross-peaks, discussed above for colon studies, correlate with increased tumorigenesis [6].…”
Section: Glycoprotein Antigens In Other Neoplasms and General Clinicamentioning
confidence: 99%
“…The amount of each sequence present in tumours and cell lines can now be explored by magnetic resonance spectroscopy (MRS) using easy to obtain twodimensional MRS images from fine-needle aspirates of tumours or cancer cell lines. Studies so far have shown different patterns of fucosylation dependent on the stage of cancer [5,61. This is an exciting new development in tumour diagnosis which we discuss here in the context of our knowledge about tumourassociated oligosaccharide changes.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no blood biomarkers with high sensitivity or specificity for potentially curable early stage CRC have been validated for clinical use, even though numerous reports have demonstrated that CRC is associated with changes in the blood proteome [4][5][6][7][8][9][10]. Currently, apart from direct macroscopic detection, there are two indirect diagnostic tools to detect CRC: one is a stool-based approach such as DNA testing [5] while the other involves testing blood levels of carcinoembryonic antigen (CEA).…”
Section: Introductionmentioning
confidence: 99%